AN ANALYSIS OF HUMOR IN “MARIO TEGUH GOLDEN WAYS” TALK SHOW - Wahyu Wahyu (Al-Din: Jurnal Dakwah dan Sosial Keagamaan, 2020)
AbstractThe use of humor is considered as one of the most important things in social communication. In this case, the writer analyzed the humor expressions appeared in a famous talk show in Indonesia, Mario Teguh Golden Ways. The research is focused on the types of humor expressed by Mario and the audiences during the show. The method of this study was descriptive qualitative since the researcher intended to obtain the conversations among the keynote speaker and participants. . The data were taken from the video of the talk show. The research subjects of this study are the keynote speaker and participants of the talk show Mario teguh golden ways “how to begin to be a richman” episode. The data collections were done as follows: first, the researcher downloaded the videos and transcribed of The Mario teguh talk show. Second, the researcher observed the videos; compared the videos and the transcriptions. Later, the researcher transcribed the parts of the transcription that contain humor to be analyzed further. The findings show that there are many humorous expressions appeared during the show. There are seven extracts which is divided into three classifications of humor; they are irony, teasing and joking. None of the humor expression can be categorized as banter or language play. All of the humor expressions are conceptual humor.Keywords – Conversation, Humor expression, talk show